Risk Management in Strategic Decision Making: A Case Study on MSMEs in Indonesia - Sulistyani, Nuraida Wahyu; Rosalia, Olyvia; Firayani; Ekobelawati , Fransiska (PT. Anagata Sembagi Education, 2025)
This research investigates the role of risk management in strategic decision-making among Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. MSMEs play a crucial role in the national economy, contributing over 60% to the Gross Domestic Product (GDP) and employing more than 97% of the labor force. However, they face significant vulnerabilities such as market fluctuations, financial constraints, regulatory changes, and operational inefficiencies. This study employs a qualitative case study method involving interviews and field observations with selected MSMEs across various sectors. The findings reveal that while MSME owners are generally aware of business risks, they often rely on intuition rather than formal risk management systems. The most common risks include market, operational, financial, and external threats. Risk identification and assessment processes are largely informal and reactive. Strategic decisions, such as product diversification or digital transformation, are often made without structured risk evaluation, increasing exposure to failure. The study concludes with policy recommendations to strengthen MSMEs’ capacity through targeted training, access to digital risk management tools, and institutional support from the government and financial institutions.